Association of Body Mass Index (BMI) and Urinary Glucose Levels with Urinary Tract Infections - Janardana, I Putu Wira; Jauhari, Pebrian; Sabariah,; Mathar, M. Ashabul Kahfi (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to investigate the association of body mass index (BMI) and urinary glucose levels with urinary tract infection (UTI) among patients at West Nusa Tenggara Provincial Hospital. A cross-sectional study was conducted at the hospital in October 2025. A total of 104 participants were selected using simple random sampling. BMI data were obtained from medical records based on body weight and height measurements recorded using a weighing scale and stadiometer. Urinary glucose data were retrieved from laboratory records and measured using a Dialab AutoLyser. Data were analyzed using univariate analysis, Spearman’s rank correlation for bivariate analysis, and ordinal logistic regression for multivariable analysis. The results showed a significant positive correlation between BMI and UTI category (correlation coefficient = 0.286; p = 0.003). Urinary glucose levels were also significantly and positively correlated with UTI category (correlation coefficient = 0.333; p = 0.001). The multivariable analysis yielded a Nagelkerke R² value of 0.186. BMI was significantly associated with UTI category (p = 0.032; OR = 1.58), as were urinary glucose levels (p = 0.003; OR = 2.80). In conclusion, BMI and urinary glucose levels were significantly associated with urinary tract infection categories among patients at West Nusa Tenggara Provincial Hospital.